Foetal arrhythmias: an enigma of the missed beats - Kulkarni, Ketki S.; Satoskar, Purnima R.; Bansal, Vandana; Kharate, Rachana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The synchronised depolarization and repolarisation of the atria and ventricles is achieved by specialised cardiac cells that generate an electrical impulse and propagate it along the conducting system in the myocardial tissue, leading to rhythmic activity of the atria and ventricles. Abnormalities of these rhythms lead to foetal arrhythmia. Methods: A retrospective observational study was conducted in a tertiary care hospital over period of one year to study the course and perinatal outcome of women with foetal arrhythmias. Results: The confinement in the study period was N=4302, of which 207(4.81%) women had foetal congenital malformations. Among them 21(0.48%) women had foetal cardiovascular abnormalities and 6(0.14%) women had foetal arrhythmias. There were two cases of maternal primary Sjogrens syndrome: one with foetal 2nddegree atrioventricular (AV) heart block with 2:1 AV conduction and another with foetal 3rd degree or complete heart block. Others were a case of Atrial premature contractions with compensatory pause, a case of Supraventricular tachycardia, one case of sinus tachycardia with non-immune hydrops and a case of foetal bradyarrhythmia with regular ectopic beats in a case of complex congenital heart disease. The course of these pregnancies, treatment options and perinatal outcome was studied. Conclusions: Foetal echocardiography and Doppler are effective tools for detection and monitoring of foetal arrhythmias. Early and correct diagnoses of arrhythmias help in management of foetal arrhythmias and multidisciplinary team-based approach gives optimum treatment results.